Spectrophotometric Determination of Platinum(IV) with Phenanthrenequinonemonosemicarbazone - Rai, H.C.; Chakraborti, I. (Asian Journal of Chemistry, 2010)
When phenanthrenequinonemonosemicarbazone (PQSC) reacts with platinum(IV) a brown precipitate is formed in heating. The precipitate is partially soluble in ethanol and chloroform and soluble in dimethylformamide. Because of the intensity and stability of the colour formed with platinum(IV) this system has been studied in detail with a view to utilize this reaction for the spectrophotometric determination of the metal.